Sosialisasi Core Tax Administration System dalam Meningkatkan Self-Assessment System pada Gen–Z di Bekasi - Cahyadi, Rony Uncok (Universitas Nusantara PGRI Kediri, 2025)
Tax is the largest state revenue in APBN, for this reason the target of tax revenue that set by government is always increased every year, and one of the method to achieve this target, the government has created a tax service administration system that provides facility for taxpayer to record, store, and submit documents, data, and/or information related to the implementation of rights and fulfillment of tax obligations, to increasing the awarness and compliance of taxpayer, or self-assessment system. The core tax administration system is part of the Tax Administration Core System Update Project which is expected that by using this integrated system, it will increasing the awareness of all people who have become taxpayers, to fulfill their tax obligations properly and correctly. Therefore, in this community service activity, socialization of the use of the core tax administration system was carried out to Gen-Z in the Bekasi area, with the purpose to increase Gen-Z's awareness in fulfilling their tax obligations. The result of this PKM is that Gen-Z increasingly understands the benefits of the core tax administration system.